Analisa Kelayakan Pembukaan Kantor Cabang Bank Syariah X di Kota Sungai Penuh - , Yuwono Fribarsa; , Boyke R. Purnomo, S.E., M.M. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Economic growth is a macroenomic indicator that describes the rate of economic growth in an area. In general, Sungai Penuh City in Jambi Provinces experiencing very rapid economic growth rate. Economic growth is mainly driven by trade, hotels and restaurants that are engines of economic growth Sungai Penuh City. In addition the economic growth Sungai Penuh City many supported by tourism sector. The growing volume of business in the city of Sungai Penuh followed by the development of market development as the commercial, hospitality, business, offices, and financial services including banking. Under these conditions, the Islamic Bank X is deemed necessary to expand the network in the Sungai Penuh City, Jambi province. In order to meet citizens needs in term of financial transactions to obtain services that operate Islamic Banking and to provide optimum service to the community with syariah principles. This study used a qualitative approach using quantitative data, which required further quantitative measurements of the targets set. Quantitative measurement is needed to facilitate the evaluation and correction by knowing the feasibility of an investment plan of development outlet branch (KC) Sungai Penuh City, Jambi Province. In a study measuring the feasibility of an investment using the payback period, net present value, profitability index, internal rate of return, and the BEP analysis.